Categorization of Malay Bengkung in the context of Malay socio-culture / Norizan Sajar - Sajar, Norizan (Universiti Teknologi MARA, 2019)
This research paper discusses the design and style of Malay bengkung. The 1950s was chosen because it is the beginning of fashion trends in Malay State. The transformation in fashion evolves every 10 years. Similarly, the design of the bengkung has also undergone its transformation. The main objective of this research is to identify and categorize the design and style of bengkung from the year 1950 until 2017. The methodology of this research will involve a qualitative method. Indeed, a method such as observing, describing, and analyzing the design and style of bengkung is applied in this research. Hopefully, this research provides broader exposure to the Malay bengkung design and definitely to the researchers and scholars in several areas. Perhaps this research benefit in preserving the tradition of “memakai bengkung” in the Malay social-cultural.